New neighborhood - Maya Takahashi 1994- (2024)
I think I miss home so much. I see Japanese language characters (symbols) and shapes all around in my neighborhood in Reykjavík. I have collected these shapes and documented them. Then, I rearranged and play with those characters to make bridge between Japan and Iceland. In the book, I invite people to join me. The book is consisted of 3 parts. Find, Convert, and Rebuild and Communicate. The layout of the book represents my own perspective, seeing Iceland with the feeling of homesickness and seeing my home, Japan, and its language in the new context here in Iceland. Like opening the box, looking into the new aspects of objects through my language glass. What do you see in this new neighborhood?